Intraparty politics and the local state: factionalism, patronage and power in Buffalo city metropolitan municipality - Mukwedeya, Tatenda Godswill (My University, 2016)
This thesis focuses on the everyday operation of the African National Congress (ANC) as a dominant party in post-apartheid South Africa. It examines the scope of intraparty politics, particularly the trajectory of factionalism in ANC local structures after 1994. Despite the dominance of the ANC in South Africa’s political field, its more recent political trajectory most particularly since it became a party of government in 1994 is much less well understood (Butler and Southall 2015: 1). The party has traditionally been studied using a top-down perspective and with a focus on elite level exchanges in which dynamics at the national level are viewed to reverberate downwards whilst drawing on information from party leaders. The contribution made by this thesis is that it offers a detailed qualitative focus on the operation of ANC intraparty politics at a local level drawing on evidence from Buffalo City Metropolitan Municipality. The overriding aim of this study which is informed by theoretical expositions on the dominant party approach and on patronage and clientelism, is to understand how factionalism in the ANC has evolved in the post-apartheid era. The thesis observes that the ANC’s political dominance after 1994 saw the gradual conflation of the party and state partly through two processes related the party’s transformative agenda. Firstly, the state itself had to be transformed to reflect the demographic composition of the country and for the most part the ANC deployed its cadres into the state who could tow the party line. Secondly, the party relied on the state as a vehicle for redistribution and the transformation of the broader political economy to achieve equity and growth. Hence black economic empowerment, state preferential procurement and other policies to uplift previously disadvantaged social groups became stepping stones for the emergent African middle and upper class. Whilst these processes transformed the state, they also fundamentally transformed the party itself as it became a site of accumulation. Intraparty contestation intensified over the limited opportunities for upward mobility provided by access to the state. The thesis argues that factionalism increasingly became characterised by patronage as competing groups within the party sought to ring-fence their political power and the opportunities for upward mobility provided by the state. This was also compounded by deepening neoliberalism whose consequences of unemployment, poverty and inequality especially at the local level led to increased dependence on the local state and the development of factionalism based on patronage politics. The thesis then explores how patronage operates in everyday practice at the local level. It shows how patron-client relationships are not merely the exchange of state resources for political support but rather they embody a field of power relations (Auyero 2001). Evidence from Buffalo City offers an important insight into how patronage exchanges are preceded by complex relationships of power that are established over time and through various enactments. The thesis demonstrates how patrons, brokers and clients exercise various forms of power every day that inform inclusion or exclusion into networks for distributing scarce state resources. It challenges views that regard factionalism and patronage as elite driven practices.
A thesis submitted to the Faculty of Humanities, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the Degree of Doctor of Philosophy in Sociology. 2016
Keywords: African National Congress; Political parties--South Africa; South Africa--Politics and government; Municipal government--South Africa